Socioeconomic status and corruption perceptions around the world. (21st April 2015) - Maeda, Kentaro; Ziegfeld, Adam
Why do citizens vary in their perceptions about the frequency of corruption? We hypothesize that those most harmed by corruption—the socioeconomically disadvantaged—should perceive corruption to be more frequent. Using multiple cross-national surveys, we find that the poor and the uneducated tend to perceive higher levels of corruption than the wealthy and the well educated. However, this relationship only holds in countries at high levels of economic development. In poorer countries, the statistical relationship is much weaker and sometimes runs in the opposite direction.